Effect of Step Height and Visual Feedback on the Lower Limb Kinematics Before and After Landing - Jangwhon Yoon (Korean Research Society of Physical Therapy, 2024)
Background: Landing from a step or stairs is a basic motor skill but high incidence of lateral ankle sprain has been reported during landing with inverted foot. Objects: This study aimed to investigate the effect of landing height and visual feedback on the kinematics of landing and supporting lower limbs before and after the touch down and the ground reaction force(GRF)s. Methods: Eighteen healthy females were voluntarily participated in landing from the lower (20 cm) and the higher (40 cm) steps with and without visual feedback. To minimize the time to plan the movement, the landing side was randomly announced as a starting signal. Effects of the step height, the visual feedback, or the interaction on the landing duration, the kinematic variables and the GRFs at each landing event point were analyzed. Results: With eyes blindfolded, the knee flexion and ankle dorsiflexion on landing side significantly decreased before and after the touch down. However, there was no significant effect of landing height on the anticipatory kinematics on the landing side. After the touch down, the landings from the higher step increased the knee flexion and ankle dorsiflexion on both landing and supporting sides. From the higher steps, the vertical GRF, anterior GRF, and lateral GRF increased. No interaction between step height and visual feedback was significant. Conclusion: Step height and visual feedback affected the landing limb kinematics independently. Visual feedback affected on the landing side while step height altered the supporting side prior to the touch down. After the touch down, the step height had greater influence on the lower limb kinematics and the GRFs than the visual feedback. Findings of this study can contribute to understanding of the injury mechanisms and preventing the lateral ankle sprain.